Development of clinical pathways to improve multidisciplinary care of high-risk pediatric oncology patients - Reschke, Agnes; Richards, Rebecca M.; Smith, Stephanie M.; Long, Adrienne H.; Marks, Lianna J.; Schultz, Liora; Kamens, Jennifer L.; Aftandilian, Catherine; Davis, Kara L.; Gruber, Tanja; Sakamoto, Kathleen M. (Frontiers in Oncology, 2022)
Clinical pathways are evidence-based tools that have been integrated into many aspects of pediatric hospital medicine and have proven effective at reducing in-hospital complications from a variety of diseases. Adaptation of similar tools for specific, high-risk patient populations in pediatric oncology has been slower, in part due to patient complexities and variations in management strategies. There are few published studies of clinical pathways for pediatric oncology patients. Pediatric patients with a new diagnosis of leukemia or lymphoma often present with one or more “oncologic emergencies” that require urgent intervention and deliberate multidisciplinary care to prevent significant consequences. Here, we present two clinical pathways that have recently been developed using a multidisciplinary approach at a single institution, intended for the care of patients who present with hyperleukocytosis or an anterior mediastinal mass. These clinical care pathways have provided a critical framework for the immediate care of these patients who are often admitted to the pediatric intensive care unit for initial management. The goal of the pathways is to facilitate multidisciplinary collaborations, expedite diagnosis, and streamline timely treatment initiation. Standardizing the care of high-risk pediatric oncology patients will ultimately decrease morbidity and mortality associated with these diseases to increase the potential for excellent outcomes.